Characterisation and Separation of Brain Wave Signals - Saadha, A.; Manic, K.S.; Pirapaharan, K. (eureca, 2014)
Neurons in the brain communicate through electrical impulses that give rise to both electrical and magnetic fields which are categorized into five different band limits. These waves can be measured outside the skull through an Electroencephalogram. The utilisation of brainwave detection in other areas such as biomedical engineering and gaming industry is yet to be explored. Categorisation of different rhythms of brainwaves and brainwave pattern analysis make it easier to identify the mental status of a person. This research aims to develop a hardware and software that is tested using function generators to simulate the EEG signal from the brain. It is observed that the initial results based on the above that the device performs as expected and hence can be used as brain wave signal measuring device.
Keywords: Brain wave; EEG; Signal processing